The mega COMBO collaboration: An individual patient data pooled analysis of patients undergoing PCI with COMBO stent. (1st January 2023) - Nardin, Matteo; Pivato, Carlo Andrea; Cao, Davide; Sartori, Samantha; Zhang, Zhongjie; Vogel, Birgit; Nicolas, Johny; Chiarito, Mauro; Qiu, Hanbo; Chandrasekhar, Jaya; Spirito, Alessandro; Abizaid, Alexandre; et al.
Abstract: Background: COMBO (OrbusNeich Medical, Hong Kong) is a dual-therapy coronary stent featuring sirolimus as antiproliferative drug and an anti-CD34+ antibody coating to attract endothelial progenitor cells favoring rapid stent re-endothelization. The Mega COMBO collaboration aimed to evaluate the performance of the COMBO stent in a large contemporary cohort of patients undergoing percutaneous coronary intervention (PCI). Methods: Patient-level data of subjects undergoing PCI with the COMBO stent from the REMEDEE-Trial, REMEDEE-OCT, HARMONEE, REDUCE, SORT OUT X, REMEDEE-Registry and MASCOT studies were pooled together. The primary endpoint was 1-year target lesion failure (TLF), a composite of cardiovascular death, target vessel myocardial infarction (TV-MI) or clinically driven target lesion revascularization (CD-TLR). Secondary outcomes were the individual components of the primary endpoint and stent thrombosis (ST). Endpoints were evaluated against performance goals based on the EAPCI (the European Association of Percutaneous Coronary Intervention) recommendations for new drug-eluting stents. Results: A total of 6753 patients (mean age 63.7 ± 11.4 years, 23% women) were included. At 1-year follow-up, TLF occurred in 303 (4.6%) patients. The rates of cardiovascular death, TV-MI, and CD-TLR were 1.3%, 1.8%, and 2.5%, respectively. The rate of definite/probable ST was 0.73%, early ST (<1 month) was 0.48%, while late ST (1–12 months) was 0.26%. The performance goals were met for all of the evaluated endpoints. Conclusions: This large patient-level pooled analysis provides a comprehensive outline of the performance of the dual-therapy COMBO stent. The low rates of primary and secondary endpoints suggest that this stent technology may be a good alternative to other contemporary drug eluting coronary stent platforms. Highlights: Despite promising early studies on the dual-therapy COMBO stent, recent randomized-controlled clinical trials have yielded mixed findings. This individual patient data analysis of 5 randomized trials and 2 prospective registries represents the largest study on patients undergoing PCI with the COMBO stent. The observed 1-year event rates favorably compared against the EAPCI performance goals for second generation DES. Characteristics of the study cohort reflect a real-world PCI population; the low rates of adverse events provide reassurance on the safety and efficacy of the COMBO stent. The COMBO stent represents a reasonable alternative to other drug-eluting stent platforms.